Myositis specific and myositis associated autoantibodies in idiopathic inflammatory myopathies: a serologic study of 46 patients - R. Rondinone; R. Bendo; M. Tonello; E. Tarricone; L. Iaccarino; S. Zampieri; A. Ghirardello; F. Cozzi; A. Doria (PAGEPress Publications, 2011)
Objective. To characterize serum autoantibody profiles of patients with idiopathic inflammatory myopathies (IIM) by searching for myositis-specific (MSA) and myositis-associated (MAA) antibodies with sensitive and specific laboratory tests. Methods. We tested the sera from 46 Caucasian patients diagnosed as affected with IIM at the Division of Rheumatology of Padova University (21 polimyositis, PM; 22 dermatomyositis, DM; 3 myositis overlap syndrome). All patients had definite IIM according to the criteria of Bohan-Peter. MSA including anti-tRNA synthetase (anti-Jo-1 and others) and anti-Mi-2 were determined by RNA immunoprecipitation and a modified immunoblot test, respectively. MAA (-U1RNP, -U2RNP, RoRNP, PM/Scl, Ku) were detected by counterimmunoelectrophoresis and immunoblot. Results. Serum MSA and/or MAA were found in 30/46 (65%) patients with IIM. Twenty-three patients (50%) were positive for at least one MSA: anti-Jo-1 in 15 (33%), anti-Mi-2 in 6 (13%), and other anti-tRNA synthetase in 3 (6%).One patient was anti-Jo-1/Mi-2 positive. Moreover, 18 patients (39%) were positive for at least one MAA: anti-Ro/SSA in 13 (28%), anti-U1RNP in 4 (9%), anti-PM/Scl in 1 (2%) and anti-Ku in 1 (2%). Coexisting MSA and MAA were observed in 8 patients (17%), anti-Jo-1/SSA positive in most cases. Anti-Jo-1 was predominantly associated with PM (57% in PM vs 14% in DM), whereas anti-Mi-2 was exclusively found in DM patients (27%). Anti-synthetase antibodies were closely associated with interstitial lung disease and polyarthritis; anti-Mi-2 positive DM patients did not have lung involvement. Notably, anti-Ro/SSA antibody was frequently observed and almost equally detected in either PM or DM (about 30%): in more than 50% of cases the antibody was associated with one MSA. Conclusions. By means of analytically reliable methods, MSA was detected in 50% of our IIM patients. Searching for MSA in patients with IIM is recommended because of its diagnostic and prognostic value.